(untitled) (Chicago, ILL, 2002)
This volume includes highly useful essays (both articles from the original edition and new ones) that focus on helping librarians better understand how public relations can help make their library as user-friendly and user-oriented as possible. The contributing writers add sound essays on marketing and development activities; writing news, photo, and press release announcements; designing library publications; creating web-based public relations and exhibits; establishing multimedia programs via touch screen kiosks and CD ROMs; planning special events; and desktop publishing.
Keywords: Libraries,Thư viện; Public relations,Quan hệ công chúng; United States,Hoa Kỳ